Analisis Stakeholder dalam Strategi Pencegahan Perkawinan Anak di Indonesia - Sri Yuliani; Rahesli Humsona; Rutiana Dwi Wahyunengseh; Tiyas Nur Haryani; Agusniar Rizka Lutfia (Universitas Sebelas Maret, 2022)
Elimination of child marriage is one of the targets of the Sustainable Development Goals (SDGs) which is targeted to be realized in 2030. To realize this goal, the Government of Indonesia has integrated the reduction of child marriage rates into the 2020-2024 National Medium-Term Development Plan (RPJMN). The child marriage rate is targeted to decrease from 11.2% in 2018 to 8.74% in 2024. In the last 10 years the number of marriages has decreased slowly and fluctuated. Even the target of reducing the number of child marriages seems to be experiencing obstacles because in 2020 the Covid 19 pandemic has contributed to a significant increase in the number of child marriages. This reality indicates that efforts to reduce the number of child marriages require a holistic and integrative effort that involves various stakeholders both in state institutions, the business world, and civil society. Considering the important role of multi-stakeholder synergy in preventing child marriage, this research aims to conduct stakeholder analysis to identify key stakeholders, primary and secondary stakeholders, their interests and influence on the success of the strategy to prevent child marriage.